2007
DOI: 10.1002/ijc.23109
|View full text |Cite
|
Sign up to set email alerts
|

EGFR induces expression of IRF‐1 via STAT1 and STAT3 activation leading to growth arrest of human cancer cells

Abstract: Recently, we reported that epidermal growth factor receptor (EGFR) induce expression of a module of genes known to be inducible by interferons and particularly interferon-c. Here we show that the module is tightly regulated by EGFR in the 2 human cancer cell lines that overexpress EGFR, A431 and HN5. The module of genes included the tumor suppressor IRF-1, which was used as a prototypical member to further investigate the regulation and function of the module. Ligand-activated EGFR induce expression of IRF-1 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 40 publications
10
35
0
Order By: Relevance
“…The role of the Src pathway downstream of growth factors is well known. In fact, Src involvement in PDGF-and EGF-mediated tyrosine phosphorylation of STAT1 and STAT3 has been reported in tumor and normal cells with different biological activity (48,49). In this report, we show for the first time the involvement of the TLR3/Src/STAT1 pathway in mediating in- …”
Section: Discussionmentioning
confidence: 58%
“…The role of the Src pathway downstream of growth factors is well known. In fact, Src involvement in PDGF-and EGF-mediated tyrosine phosphorylation of STAT1 and STAT3 has been reported in tumor and normal cells with different biological activity (48,49). In this report, we show for the first time the involvement of the TLR3/Src/STAT1 pathway in mediating in- …”
Section: Discussionmentioning
confidence: 58%
“…The observation that of the various EGFR downstream pathways only inhibition of the JAK/STAT1/3 pathway revealed changes in E2F3a expression in terms of an E2F3a upregulation (Fig. 4D), together with the knowledge that JAK/ STAT1/3 participates at least in the regulation of IRF-1 expression (27), gave rise to the hypothesis that IRF-1 could act as a repressor and IRF-2 as an activator of E2F3a expression. On the other hand, VDR is not a known component of the JAK/STAT1/3 pathway, and furthermore, treatment of ovarian cancer cell lines with 1α, 25-dihydroxyvitamin D 3 , the most active metabolite of vitamin D 3 , did not affect E2F3a mRNA levels.…”
Section: Discussionmentioning
confidence: 87%
“…17) In contrast, it has been shown that other tyrosine protein kinases such as EGF receptor and c-Src mediate phosphorylation of STAT1. 27,28) Thus, we cannot rule out the possibility that C4 and C10 inhibit STAT1 phosphorylation independently of type I IFN receptor activation by IFN-β.…”
Section: Discussionmentioning
confidence: 99%